Densification of complex shape ceramics parts by SPS. Issue 7 (July 2020) - Hocquet, S.; Dupont, V.; Cambier, F.; Ludewig, F.; Vandewalle, N.
Abstract: Spark Plasma Sintering (SPS) equipments, with higher productivity and hybrid heating modes, allow reducing thermal gradients in large samples and broaden their application potential. Furthermore, strong shape limitations remain: only simple shapes can be obtained because of the use of uniaxial pressure. The aim of this paper is to propose a SPS densification method for complex shape ceramic or powder metallurgy parts, without any modification of the tools and equipment. The samples to be sintered are placed in a powder bed in the classical die used in SPS. Different powder beds have been tested. A numerical model was developed in order to allow a rapid simulation of the force field around a part surrounded by a powder bed in a SPS tool. The optimization of the operating conditions was carried out, first, on small simple-shape samples, then, on complex geometry parts which were densified to demonstrate the feasibility of the proposed sintering process.